2016
DOI: 10.1111/epi.13294
|View full text |Cite
|
Sign up to set email alerts
|

Health and economic benefits of public financing of epilepsy treatment in India: An agent‐based simulation model

Abstract: SummaryObjectiveAn estimated 6–10 million people in India live with active epilepsy, and less than half are treated. We analyze the health and economic benefits of three scenarios of publicly financed national epilepsy programs that provide: (1) first‐line antiepilepsy drugs (AEDs), (2) first‐ and second‐line AEDs, and (3) first‐ and second‐line AEDs and surgery.MethodsWe model the prevalence and distribution of epilepsy in India using IndiaSim, an agent‐based, simulation model of the Indian population. Agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(95 citation statements)
references
References 30 publications
0
86
0
9
Order By: Relevance
“…A study conducted in India revealed that the cost per patient for epilepsy treatment was as high as 88.2% of the Indian's per capita gross national product (GNP). is epilepsy-related cost includes travel cost, lost work time, and medical costs which exceeded $2.6 billion/year [7].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in India revealed that the cost per patient for epilepsy treatment was as high as 88.2% of the Indian's per capita gross national product (GNP). is epilepsy-related cost includes travel cost, lost work time, and medical costs which exceeded $2.6 billion/year [7].…”
Section: Introductionmentioning
confidence: 99%
“…6 Epilepsy affects about 20-40 million people worldwide. 7 It is the second most common neurological disorder, after stroke. 8 The rates are similar between different ethnic groups and slightly higher for men compared to women.…”
Section: Introductionmentioning
confidence: 99%
“…6 To overcome these issues, the development of effective and accessible antiepileptic drugs is needed.…”
mentioning
confidence: 99%